HLA‐DRB1*13:01 allele in the genetic susceptibility to colorectal carcinoma. Issue 10 (30th October 2014) - Aureli, Anna; Canossi, Angelica; Del Beato, Tiziana; Franceschilli, Luana; Buonomo, Oreste; Papola, Franco; De Sanctis, Flavio; Lanzilli, Giulia; Sileri, Pierpaolo; Coppola, Andrea; Caratelli, Sara; Arriga, Roberto; et al.
<x xml:space="preserve">Abstract</x> Increasing evidence suggests that HLA‐DRB1 alleles reduce or increase the risk of developing ulcerative colitis‐associated colorectal carcinoma (CRC) tumors. However, the role of HLA‐DRB1 locus on the susceptibility to develop CRC tumor, in the absence of a history of inflammatory bowel diseases (IBDs), is unclear. The aim of our study was to determine whether HLA‐DRB1 alleles are associated with IBD‐independent CRC tumor. HLA‐DRB1 allele polymorphisms were identified by sequence‐based typing method in 53 CRC patients and 57 sex‐ and age‐matched healthy Caucasian controls. Pearson's chi‐squared analysis with Yate's correction or Fisher's exact test with Bonferroni's correction, as appropriate, were used to compare the allele frequency (AF) differences of HLA‐DRB1 in patients and controls. A total of 29 HLA‐DRB1 alleles were recognized. A detailed study of these alleles allowed to identify DRB1*13:01 and DRB1*11:01 alleles that were significantly associated with an increased and reduced risk to develop CRC tumor, respectively. AF of DRB1*13:01, in CRC patients, was significantly higher than that of healthy controls, even following Bonferroni's correction (p = 0.029). In contrast, the presence of the DRB1*11:01 allele was negatively associated with CRC tumor as evidenced by the significantly lower AF in CRC patients than that of healthy controls (p = 0.005). However, following Bonferroni's correction, the AF of DRB*11:01 lost its statistical significance. These results suggest that HLA‐DRB1*13:01 allele could be a potential marker for predicting genetic susceptibility to CRC tumor. In contrast, the protective role of DRB1*11:01 remains unclear.